Sistem Pendukung Keputusan Dalam Menentukan Supplier Jeruk Pontianak Berbasis Fuzzy-AHP - Salahuddin Salahuddin; Sri Hartati (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2012)
Orange fruit siam Pontianak or usually called Pontianak ,it is very popular to the people and the fruit itself is very favorite of many people in Indonesia because of its taste which is so sweet and a little sour and refresing. The competition of orange in industries is becoming more intense. The high preference to this orange makes it a demand in most markets  to the food industries, farmacy industry and local(traditional) medicine has point out that supplier of this orange is meeting importan factor that quarantee direct to the company. The collection of data in this survey and the sample of orange from every area is capable of producing orange Pontianak in the province of West Kalimantan. In this research will analyst the area supplier in producing standardize orange founded on the quality and the appropriate criteria based on the SNI. The method that is used is Fuzzy-AHP with weighting non-additive.The result that is used Fuzzy AHP non-additive in stating supplier of the orange pontianak in showing, attractive criteria, hygienic,sizes, marketing, , rotting is the first criteria which is undetake for giving the supplier quality orange. In examining the level of consistency using the method Fuzzy AHP non-additive is made in every structural level, hierarchal system is capable of handling the non consistency in the end testing, then will obtained the best supplier with important criteria for the company.